ESTUDIO DE FACTIBILIDAD PARA LA CREACIÓN DE UNA LAVADORA AUTOMOTRIZ PARA VEHÍCULOS LIVIANOS EN LA PARROQUIA VILCABAMBA DEL CANTÓN LOJA - Simón Garcia, Fanny Tamara (2015)
Currently the washing of light vehicles in the parish of Vilcabamba are scarce causing problems and disadvantages in the vehicle owners. This feasibility project aims to install a company wash for light vehicles in the parish of Vilcabamba, which was located on the outskirts of the same through this innovative service assisted with the best service you would provide that you can give the customer to achieve satisfaction. This company will be located in the parish of Vilcabamba and directed to light vehicles. The methodology used to achieve the objectives related to: the deductive and inductive method, with the techniques and tools developed for this purpose. In this project feasibility is underpinned by various studies carried out, such as: The market study which identified the potential that is 1195 demand, real demand is 1101, the effective demand for 953 families who own vehicle which was multiplied by the average number of services is 47 per year obtaining a total of 44796 services a year, offer service car wash is 1300 per year, identifying unmet demand for 43496. In the study of technical installed capacity it is 26280 and services used is capable services in the year 7488 was determined; the location is determined according to the Macro Trace is in the Province of Loja, and microlocalization is in the parish of Vilcabamba in the sector Cucanama upper town. 5 With regard to financial study calculating the resources required for the installation and operation of the washer and funding sources it was determined performed; the calculation of the total investment, total costs, unit costs and revenues of the service, which are backed in their respective budgets, essential elements for the Financial Evaluation in which the viability of the project was verified was also performed. Finally he reached the following conclusions: the project has a net present value (NPV) of $ $ 29,561.26, Internal Rate of Return (IRR) of 28.25%, Benefit Cost Ratio (B / C) 1.88, Capital Recovery Period (PRC) 2 years, 8 months and 26 days and the sensitivity analysis indicates that it supports an increase of 47.92% in costs and a decrease of 25.77% in revenue, demonstrating that the project is feasible to be made is therefore appropriate implementation. Finally, conclusions and recommendations that this study came after the end are described.